Software Development using Object-First Approach: a New Learning Strategy - Gurdeep S Hura (Journal of Education and Learning (EduLearn), 2017)
Software Engineering approach deals with the Software Development (SD) that is aligned with design and development of software applications. The Software Development may be implemented in a variety of techniques but its implementation using a procedural paradigm and an imperative language seem to be more effective and efficient for the design and implementation of software applications. The procedural approach for Software Development offers advantages as this it may be used to teach some basic features of programming languages. The object of this paper is to introduce the software development and associated object-first approach for the design of software project application using top-down method. This approach defines functions and modules as basic units for the design and implementation and also for offering hands-on experiences with the basics of programming languages of sequences, selections, iterations structures. These structures will be used to define various modules with programming language constructs for of software development process. The software Development process is one of the very crucial processes of software engineering.